Reliability of renal point-of-care ultrasound (POCUS) performed by pediatric postgraduates to diagnose hydronephrosis in infants - Cheon, Eun Jung; Yoon, Jung Min (Frontiers in Pediatrics, 2024)
Purpose: Point-of-care ultrasound (POCUS) has gained prominence in a variety of medical specialties due to advances in ultrasound technology. POCUS has not been fully integrated into pediatric residency training programs despite its widespread use and proven benefits. At our institution, renal POCUS is performed by pediatric residents for the evaluation of hydronephrosis, which is the main pathology for which ultrasound is used in the clinical practice of pediatric nephrology. This study was conducted to evaluate the quality of renal POCUS performed by pediatric residents in infants. Methods: Four pediatric residents, comprising two first-year and two second-year residents at Konyang University Hospital, participated in the study conducted from May 2021 to May 2022. All participants had completed our Point-of-Care Ultrasound (POCUS) training program.The study focused on infants admitted to the pediatric inpatient unit, identified by attending physicians as requiring renal ultrasound. All infants underwent their initial kidney ultrasound examination. Temporal alignment between renal Point-of-Care Ultrasound (POCUS) performed by pediatric residents and conventional ultrasound (USG) conducted by radiologists was asynchronous. Pediatric residents conducted POCUS sessions during scheduled radiologist appointments throughout the day, occurring either before or after the radiologist's examination. There was no mutual awareness of each other's results. Inter-observer agreement between radiologists and pediatric residents was compared for the presence or absence of hydronephrosis and its grade, which are primary considerations in pediatric renal ultrasound. Results: Our study found that 53 infants (68.8%) were diagnosed with hydronephrosis using point-of-care ultrasound (POCUS), compared to 48 infants (62.3%) diagnosed with conventional ultrasound (USG). Among the POCUS examinations conducted by pediatric residents, hydronephrosis of SFU grades 1, 2, 3, and 4 were observed in 56.6%, 35.8%, 7.5%, and 0%, respectively. Inter-observer reliability between POCUS and conventional USG showed good agreement, with Cohen's kappa coefficients exceeding 0.8 for sensitivity and 0.6 for grading. Conclusions: Renal POCUS performed well in diagnosing and grading hydronephrosis in infants when performed by pediatric residents who had completed a two-phase training program.